PREPARATION AND CHARACTERIZATION OF ALGINATE/METHYL CELLULOSE MICROBEADS OF LOSARTAN POTASSIUM - MAHENDRASINH M. RAJ; LATA M. RAJ; HEMUL V. PATEL; ANIL K. PATEL (International Journal of Pharma and Bio Sciences, 2015)
Losartan Potassium microbeads were formulated by ionotropic gelation technique using a combination of sodium alginate and methyl cellulose. The influence of different concentrations of polymer was studied. Microbeads were assessed for their physicochemical properties and In-vitro drug release studies. FT-IR study confirmed that there was no drug excipient interaction. The prepared microbeads are within specifications for all the physicochemical properties.SEM shows all the beads are spherical and smooth surface. In-vitro release data shows the individual concentration of sodium alginate sustains the drug release up to 8hrs but combinations with methyl cellulose sustain the drug release more than 12 hrs. Methyl cellulose in higher proportion increased the mean diameter of bead and increased encapsulation efficiency up to 93.94 % and drug release was extended up to 13hrs.